Mechanisms of Heavy Metal Toxicity at the Cellular, Molecular and General Health Levels - Ameera Jasim Al-Aaraji Oudah; Ruwaida Wahab Salman AL-Jebory; Ahmed Hasan R. Al.Zurfi; Jasim, Haider Mahmod (Journal of Biomedicine and Biochemistry, 2025)
Heavy metals such as lead, mercury, arsenic, and cadmium are ubiquitous environmental contaminants that pose significant health hazards. These metals disrupt normal cellular processes by inducing oxidative stress, lipid peroxidation, and DNA damage. On the molecular level, they interfere with enzymatic functions, disrupt calcium homeostasis, and trigger apoptosis or necrosis. Chronic exposure is linked to carcinogenesis, neurotoxicity, nephrotoxicity, and endocrine dysfunctions. This review examines the cellular and molecular mechanisms underlying heavy metal toxicity, highlighting recent findings on oxidative stress pathways, mitochondrial dysfunction, and inflammatory responses. It also discusses current strategies for detoxification and the role of chelation therapy. Better understanding these mechanisms is vital for developing preventive measures and therapeutic interventions to mitigate toxic effects.